2012
DOI: 10.1007/s00410-012-0786-9
|View full text |Cite
|
Sign up to set email alerts
|

Platelet development in cuboid diamonds: insights from micro-FTIR mapping

Abstract: Fourier transform infrared mapping of diamonds can reveal detailed information on impurities, with a spatial context. We apply this technique, combined with in situ isotopic analysis of carbon, to the study of cuboid diamond growth in a sample that exhibits some mixedhabit growth. While there has been some uncertainty in the literature regarding sectoral differences in nitrogen aggregation and subsequent platelet development, the data from this study appear far more conclusive. We show that despite nitrogen be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…It is well known that the formation of the twinned micro-lamellae is an important mechanism for deformation accommodation in diamond [37]. Previous high-pressure and high-temperature (HP-HT) experiments carried out on synthetic diamonds suggested that the {111} micro-twins begin to form under a range of P and T conditions typical for the upper mantle [26,38,39]. Howell et al (2012) [26] showed that further differential stress brings a continuous crystal bending that produces the formation of subgrains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the formation of the twinned micro-lamellae is an important mechanism for deformation accommodation in diamond [37]. Previous high-pressure and high-temperature (HP-HT) experiments carried out on synthetic diamonds suggested that the {111} micro-twins begin to form under a range of P and T conditions typical for the upper mantle [26,38,39]. Howell et al (2012) [26] showed that further differential stress brings a continuous crystal bending that produces the formation of subgrains.…”
Section: Discussionmentioning
confidence: 99%
“…Previous high-pressure and high-temperature (HP-HT) experiments carried out on synthetic diamonds suggested that the {111} micro-twins begin to form under a range of P and T conditions typical for the upper mantle [26,38,39]. Howell et al (2012) [26] showed that further differential stress brings a continuous crystal bending that produces the formation of subgrains. In particular, when multiple slip systems {111} <110> occur simultaneously, a rotation of subgrains arises around <112> axes.…”
Section: Discussionmentioning
confidence: 99%
“…However, two recent studies (Howell et al, 2012;2013a) have shown compelling evidence that the rate of nitrogen aggregation does not differ between sectors, but that the subsequent rate of platelet formation can be retarded in cuboid sectors due to the presence of "disc-crack-like" defects (Walmsley et al, 1987). Hydrogen-related absorption features are significantly stronger in the cuboid sectors (Rondeau et al, 2004;Howell et al, 2012;2013a), most likely due to C-H bonding occurring on the internal surfaces of the disc-crack-like defects. However, due to the possible abundance of IR-inactive hydrogen within a diamond (Sellschop, 1992;Sweeney et al, 1999), there remains no quantitative evidence regarding hydrogen partitioning between growth sectors.…”
Section: Introductionmentioning
confidence: 95%
“…Carbon-isotope analysis via both gas-sourced mass spectrometry (Cartigny et al, 2003) and secondary-ion mass spectrometry (SIMS; Bulanova et al, 2002;Zedgenizov & Harte, 2004;Howell et al, 2012;2013a) has revealed no evidence of isotopic fractionation between the growth sectors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation